2010
DOI: 10.1007/s11095-010-0276-6
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Strategy for the Synthesis of Biocompatible Gold Nanoparticles Using Cinnamon Phytochemicals for Phantom CT Imaging and Photoacoustic Detection of Cancerous Cells

Abstract: Purpose. The purpose of the present study was to explore the utilization of cinnamon coated gold nanoparticles (Cin-AuNPs) as CT/optical contrast enhancement agent for detection of cancer cells.Methods. Cin-AuNPs were synthesized by a -Green‖ procedure and the detailed characterization has been performed by physic-chemical analysis. Cytotoxicity and cellualar uptake studies were carried out in normal human fibroblast and cancerous (PC-3 and MCF-7) cells respectively. The efficacy of detecting cancerous cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 41 publications
0
80
0
1
Order By: Relevance
“…We envisioned that radioactive gold nanoparticles, which are inherently therapeutic, present realistic prospects in achieving optimal therapeutic payloads in prostate tumors because of their (i) size, (ii) inherent affinity toward tumor vasculature, and (iii) most importantly, their favorable radiochemical properties (19)(20)(21). Au-198 provides a desirable beta energy emission and halflife that destroys tumor cells/tumor tissue (β max ¼ 0.96 MeV; half-life of 2.7 d) (18).…”
mentioning
confidence: 99%
“…We envisioned that radioactive gold nanoparticles, which are inherently therapeutic, present realistic prospects in achieving optimal therapeutic payloads in prostate tumors because of their (i) size, (ii) inherent affinity toward tumor vasculature, and (iii) most importantly, their favorable radiochemical properties (19)(20)(21). Au-198 provides a desirable beta energy emission and halflife that destroys tumor cells/tumor tissue (β max ¼ 0.96 MeV; half-life of 2.7 d) (18).…”
mentioning
confidence: 99%
“…It has been reported that some Ag nanoparticles produce significant toxicity in cell culture media, 34 while protein-coated Ag nanoparticles show minimal or no toxicity in a 3T3 cell culture, which is consistent with the results of cinnamon phytochemical-coated Au nanoparticles. 35 A possible explanation is that both of these are naturally occurring biomolecules that have evolved and have been proven safe in the human body. 36,37 They supply a nontoxic coating for Ag nanoparticles, which provides biocompatibility for in vivo administrations.…”
mentioning
confidence: 99%
“…Based on our pioneering efforts in green nanotechnology and Nano medicine, Chanda et al [32], Katti et al [33], Shukla et al [34], Mukherjee et al [35], are exploring to enhance the therapeutic payloads of biologically active phytochemicals in broccoli. Nanotechnology in herbal medicine would therefore allow storage, efficient transport and delivery of reservoir of phytochemical cocktails into the cellular matrix.…”
Section: Uv-vis Absorbance Spectroscopy Analysismentioning
confidence: 99%